Virtual Reality (VR) in chemistry learning for secondary schools students / Muhammad Nabil Shah Zafarin and Chew Chiou Sheng - Zafarin, Muhammad Nabil Shah; Chew, Chiou Sheng (College of Computing, Informatics, and Mathematics, 2024)
This research aims to create a chemistry learning application using virtual reality and the Unity Game Engine. The focus is on secondary school students, providing an interactive, immersive experience that helps them understand scientific concepts by visualizing chemical reactions. The complexity of Virtual Reality (VR) in learning chemistry for secondary school is the effective implementation of VR in chemistry education requires addressing the diverse learning needs of students, providing access to appropriate technology, and ensuring that the VR experiences align with the curriculum standards and learning objectives. Traditional methods of learning chemistry are less attractive than what is needed to deal with this complexity, requiring the development of innovative solutions. The proposed approach utilizes a 3D simulation game using the Simulation-Based Edutainment Model in the ADDIE methodology to enhance deep learning among students. Virtual Reality (VR) is widely recognized as an effective tool for improving learning outcomes. Creating a fully interactive and immersive experience enables students to practice and apply their knowledge in a realistic simulation of real-life situations. The Virtual Reality (VR) in Chemistry Learning for Secondary School Students uses the systematic approach of the ADDIE Model to analyse, design, develop, implement, and evaluate VR applications enables instant feedback, personalized learning experiences, and the ability to revisit and review the content, improving student understanding and retention of complex concepts. The ADDIE Model was chosen as a methodology to create a VR experience with good instructional learning and is acceptable as an alternative way of learning. The usability evaluation conducted through the System Usability Score (SUS) questionnaire produced positive results with a score of 91.25%, demonstrating the effectiveness of Virtual Reality applications in improving chemistry learning for high school students. Future work will enrich the immersive VR chemistry education platform through advancements like realistic liquid simulations, simulated breakage, multiplayer capabilities, and enhanced physics realism, promoting collaborative learning among high school students.